Flugschriften As A Key Medium Of The Reformation: Texts And Images - Котляров, Петро (Київський національний університет імені Тараса Шевченка, 2018)
Pamphlets (Germ. Flugschrift or Flugblatt) became an important medium during the European Reformation. This paper looks at Flugschriften as a driver for the new religious teaching and a phenomenon in social and cultural life in the Sixteenth century Germany. We pay special attention to the use of Flugschriften by reformers as a mean of communication with different social strata (as with educated elite, so with illiterate people). We found that popularity of Flugschriften relied heavily on the reformers’ activities. They need to communicate new ideas to their sympathizers, which, in their turn, were interested in following events and discussions, finding new arguments for the opponents. Due to the low prices for pamphlets, they appeared even in very poor houses previously deprived of any written or printed word. One can notice how engravings from Flugschriften had better reflected any minor changes in public image of the main reformers, than any other document. Authors of pamphlets elaborated a visual language on its own and, for this purpose, reconsidered Catholic iconography. For example, Hans Baldung Grien in his engraving from 1521 depicted Martin Luther as a righteous man with traditional Catholic iconography features. On the one hand, in this way he made image understandable for, who had recently left Catholicism for Lutheran teaching. On the other hand, this interpretation of Luther’s image as a righteous warrior against Papacy coincided with Luther’s own ideas concerning his mission and with his followers’ ones, which looked for radical changes in religious and social life. Luther’s’ engraved portraits became a departing point for a brand new Protestant iconography. It combined visual and narrative hints on Luther as a fighter against “the Old Church”, which relies solely on the Bible. However, to make these images work artists often used Catholic symbols and iconographical types.

Летючі листки (нім. – Flugschrift, або Flugblatt) - важливий медійний засіб доби європейської Реформації. У статті автор аналізує особливості феномену летючих листків як перших медіа у поширенні нових ідей, їх місце у соціальному і культурному житті Німеччини. Встановлено, що популярність летючих листків була пов’язана з тим, що вони виявилися важливим комунікативним засобом в межах реформаційної спільноти. Звернено увагу, що гравюри, присутні на сторінках летючих листків, більшою мірою, ніж інші документи, відтворюють історію творення образів діячів Реформації. З’ясовано, що на гравюрі Ганса Бальдунга Гріна (1521 р), художник зображуючи Мартіна Лютера, свідомо застосовав звичну для релігійного мистецтва іконографію, щоб  образ «нового праведника» був би максимально схожий на традиційний католицький і зрозумілий для тих, хто нещодавно вийшов із католицизму. Гравюрні портрети керівника Реформації стали початком формування нової протестантської іконографії.
Летючі листки як ключове медіа доби Реформації: тексти і образи
Keywords: Flugschrift; Flugblatt; pamphlet; medium; communication; the Reformation; Martin Luther; iconography; engraving; Flugschrift; Flugblatt; трактат; медіа; комунікація; Реформація; Мартін Лютер; іконографія; гравюра